2021
DOI: 10.3390/cancers13061473
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Signaling as the Untact Mode during Signaling in Metastatic Breast Cancer

Abstract: Metastatic features of breast cancer in the brain are considered a common pathology in female patients with late-stage breast cancer. Ca2+ signaling and the overexpression pattern of Ca2+ channels have been regarded as oncogenic markers of breast cancer. In other words, breast tumor development can be mediated by inhibiting Ca2+ channels. Although the therapeutic potential of inhibiting Ca2+ channels against breast cancer has been demonstrated, the relationship between breast cancer metastasis and Ca2+ channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 176 publications
(122 reference statements)
0
4
0
Order By: Relevance
“…Rather, the activity of IP 3 Rs represents the summative effects of various modifiers including accessory proteins, and factors such as ions, nucleotides, and redox status[1].The different modes of regulation of IP 3 R by accessory proteins provides the means to alterCa 2+ signals depending on cell type and physiological status. Significantly, there is a growing number of examples where the modulation of IP 3 R-mediated Ca 2+ signals by accessory proteins is hijacked by cancer cells to provide a survival or metastatic advantage[13,[45][46][47][48][49][50][51].The present work suggests that PKM2 may similarly provide an advantageous modulation of IP 3 R-mediated Ca 2+ signals in cancer. PKM2 is highly expressed in cancer cells, where in most cases its expression correlates with poor prognosis[52].…”
mentioning
confidence: 60%
“…Rather, the activity of IP 3 Rs represents the summative effects of various modifiers including accessory proteins, and factors such as ions, nucleotides, and redox status[1].The different modes of regulation of IP 3 R by accessory proteins provides the means to alterCa 2+ signals depending on cell type and physiological status. Significantly, there is a growing number of examples where the modulation of IP 3 R-mediated Ca 2+ signals by accessory proteins is hijacked by cancer cells to provide a survival or metastatic advantage[13,[45][46][47][48][49][50][51].The present work suggests that PKM2 may similarly provide an advantageous modulation of IP 3 R-mediated Ca 2+ signals in cancer. PKM2 is highly expressed in cancer cells, where in most cases its expression correlates with poor prognosis[52].…”
mentioning
confidence: 60%
“…In the tumor microenvironment and especially at metastatic sites, Ca 2+ is a predominant but one of the least studied factors in TNBC biology. Although it is well established that circulating Ca 2+ is associated with cancer progression ( 9 , 10 ), the effects of high Ca 2+ on tumor growth varies from one cancer type to another ( 54 , 63 , 64 ). For instance, high extracellular Ca 2+ inhibits the proliferation of colon cancer and parathyroid cells ( 54 , 65 ) but stimulates both the proliferation and metastatic potentials of breast and prostate cancer cells ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that calcium signaling pathways are essential to cancer progression. In particular, calcium signaling pathways regulate key processes, from inflammation to apoptosis, that are involved in breast cancer tumorigenesis, [52] metastasis, [53] and resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%